Relationship between Treasury bill rate and NEPSE index in Nepal - Gurung, Rajesh (Pravaha, 2020)
This study has examined the relationship between 91-days Treasury bill rate and NEPSE Index with the use of annual time series data taken from Mid-July1994 to Mid-July 2018 in the context of Nepal. Time series are stationary at first differenced and they are co integrated in order 1, i.e., I (1). Error Correction Model (ECM) confirms the long-run causality from 91-days Treasury bill rate (INT) to NEPSE Index (IND) at 5 percent level and long-run causality from IND to INT at 10 percent level. This bi-directional causality implies that the interest rate policy of Nepal Rastra Bank considerably influences in the stock market performances in long-run as well as the investors’ decisions in choices between stock market and bank deposits. This finding justifies the theoretical underpinning of impact of cost of capital in business investment decisions and demand for and supply of securities in capital markets. However, Wald statistics for joint short-term coefficients of variables under the interest does not support for shortruncausality between them. This finding justifies the theoretical underpinning that low cost of capital crucially linked to create the demand for and supply of securities through business investment opportunities. Higher interest rate, in other hand, not only discourage the businesses to use credit but also stimulate investors to switch to bank deposits causing decline in stock prices.